Depression Pricing and the Depreciation Function - Bain, Joe S. (Quarterly Journal of Economics, 1937)
Journal Article Depression Pricing and the Depreciation Function Get access Joe S. Bain Joe S. Bain Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 51, Issue 4, August 1937, Pages 705–715, https://doi.org/10.2307/1881687 Published: 01 August 1937